Magnetically driven in-plane modulation of the 3D orientation of vertical ferromagnetic flakes - Le Ferrand, Hortense (2022)
External magnetic fields are known to attract and orient magnetically responsive colloidal particles. In the case of 2D microplatelets, rotating magnetic fields are typically used to orient them parallel to each other in a brick-and-mortar fashion. Thanks to this microstructure, the resulting composites achieve enhanced mechanical and functional properties. However, parts with complex geometry require their microstructure to be specifically tuned and controlled locally in 3D. Although the tunability of the microstructure along the vertical direction has already been demonstrated using magnetic orientation combined with sequential or continuous casting, controlling the particle orientation in the horizontal plane in a fast and effective fashion remains challenging. Here, we propose to use rotating magnetic arrays to control the in-plane orientation of ferromagnetic Nickel flakes distributed in uncured polymeric matrices. We experimentally studied the orientation of the flakes in response to magnets rotating at various frequencies and precessing angles. Then, we used COMSOL to model the magnetic field from rotating magnetic arrays and predicted the resulting in-plane orientations. To validate the approach, we created composites with locally oriented flakes. This work could initiate reverse-engineering methods to design the microstructure in composite materials with intricate geometrical shapes for structural or functional applications.